Productivity of pickling cucumber in the São Francisco Valley, Brazil - Resende, Geraldo Milanez de; Flori, José Egidio (Pesquisa Agropecuaria Brasileira, 2003)
With the objective of indicating pickling cucumber cultivars of high productivity, two field experiments were carried out in Petrolina, Pernambuco State, Brazil, from May to August of 1997. The experimental design was a randomized complete block with 18 treatments and three replications. Experimental plots consisted of four rows of 3 m long, and the plants were on a 1.00x0.30 m spacing grid. The commercial fruits were classified as pickling (fruits length from 6 to 12 cm) and cornichon (from 4.0 to 5.5 cm). The cultivars Eureka (34.54 t/ha) and Francipak (33.72 t/ha) presented the highest yield for pickling. The cultivars Pioneiro, Vlaspik and Wisconsin SMR 18 showed the lowest yield varying from 21.43 to 23.45 t/ha. There was a variation from 30.74 to 37.79 g/fruit and from 9.01 to 14.81 fruit/plant. For cornichon stood out the cultivars Vlasset and Supremo, followed by Vlasstar and Prêmio which showed yield above 10.00 t/ha. The lowest yield was presented by Wisconsin SMR 18, with 5.61 t/ha. There was a variation from 6.09 to 7.27 g/fruit and 11.48 to 24.15 fruits/plant.